3D-printed chitosan-based scaffolds: An in vitro study of human skin cell growth and an in-vivo wound healing evaluation in experimental diabetes in rats. (1st November 2018) - Intini, Claudio; Elviri, Lisa; Cabral, Jaydee; Mros, Sonya; Bergonzi, Carlo; Bianchera, Annalisa; Flammini, Lisa; Govoni, Paolo; Barocelli, Elisabetta; Bettini, Ruggero; McConnell, Michelle
Highlights: Microstructure conferred by 3D printing is critical for cell growth on chitosan scaffolds. Demonstration of biocompatibility of 3D printed chitosan scaffolds. Comparison of fibroblast and keratinocyte cell growth on 2D and 3D surfaces. Efficacy of 3D chitosan scaffolds for treatment of wounds in a diabetic rat model. Abstract: The fabrication of porous 3D printed chitosan (CH) scaffolds for skin tissue regeneration and their behavior in terms of biocompatibility, cytocompatibility and toxicity toward human fibroblasts (Nhdf) and keratinocytes (HaCaT), are presented and discussed. 3D cell cultures achieved after 20 and 35 days of incubation showed significant in vitro qualitative and quantitative cell growth as measured by neutral red staining and MTT assays and confirmed by scanning electron microphotographs. The best cell growth was obtained after 35 days on 3D scaffolds when the Nhdf and HaCaT cells, seeded together, filled the pores in the scaffolds. An early skin-like layer consisting of a mass of fibroblast and keratinocyte cells growing together was observed. The tests of 3D printed scaffolds in wound healing carried out on streptozotocin-induced diabetic rats demonstrate that 3D printed scaffolds improve the quality of the restored tissue with respect to both commercial patch and spontaneous healing.